Towards the Semantic E-Government - Robert BUCHMANN; Radu MEZA (Transylvanian Review of Administrative Sciences, 2012)
E-government is quite a late achievement of the information society, although in theory, it could have been the first application of the Internet, since Internet itself started as a governmental project. Many factors have been delaying the implementation of e-government, the most important ones being the digital divide, the privacy and security concerns and the availability of common data models on a national and international scale. Since its implementation comes much later than other on-line organizational models (e-business, social networks etc.), e-government also lags technologically. In Romania, but not only, e-government and public administration applications are data-driven rather than knowledge-driven, since databases are quite popular and robust as a standard model for storing the information behind traditional Web applications. On the other hand, the World Wide Web authorities invest a great deal of effort in raising the awareness of the so-called “knowledge society”, defining formalizations for knowledge-aware applications. The paper discusses the threshold between data and knowledge, the implications of the knowledge society on e-government and public administration, and proposes a knowledge generation methodology based on existing data-driven systems